Serum NT-proBNP levels in diabetes and its association with obesity, inflammation and glycemic status - Saurav Dey; Swati Bhattacharyya; Sinharay, Manali (Asian Journal of Medical Sciences, 2024)
Background: Type 2 diabetes mellitus (T2DM) patients are more prone to develop cardiovascular complications, and there is a dire need of a routine screening tool for risk assessment of heart failure (HF) in them. Aims and Objectives: The current study was conducted to estimate the levels of serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentrations in subjects with and without T2DM and evaluate the association between NT-proBNP and body mass index (BMI), waist circumference as markers of obesity, hemoglobin A1c (HbA1c), plasma fasting blood sugar (FBS), plasma postprandial blood sugar (PPBS),duration of diabetes as markers of glycemic control and serum C-reactive protein (CRP),an inflammatory marker in diabetic subjects. Materials and Methods: A hospital-based cross-sectional non-interventional study was done with 82 non-diabetic healthy volunteers and 82 T2DM patients. Anthropometric measurements (waist circumference [WC] and body mass index [BMI]) were recorded, and blood was analyzed for serum NT-proBNP, C-reactive protein (CRP), plasma fasting blood sugar (FBS), postprandial blood sugar (PPBS), and hemoglobin A1c (HBA1c). Data collected were analyzed by statistical software with P<0.05 as the significance level. Results: Serum NT-proBNP level was significantly higher in diabetic group (P<0.001) compared to non-diabetic group statistically. Correlation analysis in diabetic subjects showed a significant positive correlation of NT-proBNP with CRP (ρ+0.576, P<0.001), duration of diabetes (ρ+0.780, P<0.001), plasma FBS (ρ+0.524, P=0.003), plasma PPBS (ρ+0.673, P=0.013), and HbA1c (ρ+0.571, P=0.001) but there was no statistically significant correlation of NT-proBNP with BMI or WC values although the correlation was negative for both. Conclusion: The present study provides a novel perspective that measuring serum NT-proBNP may help in the earlier identification of impending HF in diabetic individuals assisting in prompt intervention which may be further confirmed by larger studies.